The Effect of Bilimbi Juice Levels and Soaking Time on The Growth of Aspergillus flavus, L. in Corn Kernels - Jatmiko Susilo; Agitya Resti Erwinarti; Zaira Ri Apriarti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2020)
produces aflatoxin compounds that are hepatocarcinogenic. The study intends to analyze the effect of concentration and soaking time of corn kernels in bilimbi (Averrhoa bilimbi) juice on the growth of Aspergillus flavus. The experimental research, corn kernels soaked in star fruit juice concentrations of 5, 10, and 15% v/v, for 10, 20, and 30 minutes. Corn kernels are taken and planted in AFPA media. Microscopic observations every hour to observe the growth of Aspergillus flavus from planting to growth. Data were analyzed using two-way ANOVA, followed by LSD test with 95% CI. Research shows there is a decrease in pH caused by increased levels of star fruit juice. Concentrations of bilimbi fruit and soaking time can inhibit the growth of Aspergillus flavus in corn kernels. The optimal inhibitory potential was found at 15% v/v with a soaking time of 30 minutes.